Determination of Trace Elements and Heavy Metals in Coconut Meat Simultaneously by ICP-MS - Zhang, Yanbei; Rui, Yukui (Asian Journal of Chemistry, 2013)
With the development of society, a lot of new food are explored, but their nutrition and safety is not very clear. Five macroelements and eight trace elements present in coconut meat were determined by ICP-MS. The results showed coconut meat contained the rich nutrition of macroelements which are helpful to human health. Ti, Cr, Mn, As, Se, Mo, Cd and Pb in coconut meat were exceeded the national standard. So coconut meat are not safe as food.